Fabric magnético em red beds da Formação de Conraria, Portugal Central - C.R. Gomes (2010)
The main goal of this study was to quantify the magnetic fabric on rock samples of the upper subunit of the Conraria Formation, Silves Group, in the region of Coimbra. Studies of Anisotropy of Magnetic Susceptibility (AMS) were carried out on 50 samples from 11 sites in order to characterise the magnetic fabric. The general parallelism between an oblate fabric and stratification may indicate a combination between the primary sedimentary arrangement and another one with origin in the diagenesis or even in components of earlier tectonic origin